Associations of secondary spontaneous pneumothorax characteristics with key clinical outcomes – a prospective cohort study - Eleanor C. Barton; Fiona C. Warren; Sirui Zheng; Jenny Symonds; Emma Tucker; Karl Jackson; Catharine Pearce; Megan Fahy; Poh Chai Tan; Wafa Hassan; Kay Por Yip; Beenish Iqbal; et al. (ERJ Open Research, 2026)
Background Evidence guiding management and prognostication of secondary spontaneous pneumothorax (SSP) is scarce. We describe characteristics and outcomes of SSP patients in a prospective UK cohort. Methods Multi-centre, prospective, observational cohort study of patients presenting with SSP to 21 UK hospitals over 6 months. Predictors of time to discharge, time to spontaneous resolution and 6-month mortality were analysed using competing risks survival analysis, Cox and logistic regression. Results Of 213 recruited patients, 138 (65%) were male; median age was 68 years. 155 (73%) underwent immediate pleural intervention; 58 (27%) received initial conservative management, of whom 4 subsequently underwent intervention. Median time to discharge was 8 days (IQR 4–21 days). Median time to spontaneous resolution was 3 days (IQR 1–9 days). All-cause 6-month mortality was 22% (n=46). Longer time to discharge was associated with increasing frailty (Subhazard ratio (sHR) 0.29, 95% CI 0.20–0.42), recent exacerbation (sHR 0.66, 95% CI 0.47–0.92) and intervention (0.34, 95% CI 0.22–0.55). Large intercostal chest drains (HR 0.57 95% CI 0.32–0.99), and recent exacerbation (HR 0.61, 95% CI 0.8–0.97) were associated with longer time to spontaneous resolution. Increasing frailty was associated with increased 6-month mortality (OR 10.89, 95% CI 4.03–29.42). Discussion This represents the largest prospective SSP cohort study to date. These data describe the SSP population and predictors of time to discharge, persistent air leak and mortality. Frailty was associated with poorer outcomes. Recent exacerbation and larger bore chest drain were associated with increased risk of PAL. Conservative management was commonly used, successfully in most cases.